Sony Corporation / Nur Zakira Ain Zamrun - Zamrun, Nur Zakira Ain (2022)
This assignment is about identifying the problems with the chosen product from the same company. The company that I have chosen is Sony Corporation, while from their various electronic devices, I chose to do the Sony ZV-1 digital camera for the detail analysis. In this case study, I have done the SWOT analysis to identify the strength, weaknesses, opportunities and threats of the ZV-1. The main problem that I gained on this product is that the poor performance of battery life, since the capacity of battery NP-BX1 is 1240 mAh only. From the problem, I can come up with the best solution which is adding solar panel for solar recharging capabilities for ZV-1 that have been identified their advantages and disadvantages thoroughly. The best solution is being chosen between the three solutions that I can come out with after being analyzed all of their pros and cons.